Digital citizenship trend in educational sphere: A systematic review - Wibowo Heru Prasetiyo; Noor Banu Mahadir Naidu; Bee Piang Tan; Bambang Sumardjoko (International Journal of Evaluation and Research in Education (IJERE), 2021)
The surge of information in the digital age has impacted social problems. Accordingly, digital citizenship had been discussed mostly within topics related to digital security, IT education. A systematic review is needed to provide an overview for educators and policymakers in Indonesia to address ethical and technical issues to improve the online environment safely. However, there are limited studies that systematically review the existing literature on implementing digital citizenship in Indonesia. The present study was guided by PRISMA review protocol using three databases, i.e., Scopus, Google Scholars, and ProQuest, concerned with digital citizenship, digital competence, digital literacy, and information and communications technology (ICT) skills. There were 205 articles screened; this study obtained 20 articles that fit the predetermined inclusion criteria. This study used content analysis to encode, organize categories, and develop the themes. Based on the thematic analysis, this study has three main themes namely digital readiness, digital citizenship competencies, and educational policies. This review contributes to the existing literature by providing direction to future study and embedded digital citizenship competencies in the educational setting as a catalyst for a new literacy.